Continuous linked settlement (CLS) - Bech, Morten; Martin, Antoine (Henry Stewart Talks, 2010)
Overview of the FX market, The economic role of CLS, How has CLS changed FX settlement?, How is CLS organized?, The effect of CLS on international payments, Future directions for CLS and regulatory implications